2016
DOI: 10.1017/s2040174416000428
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency, behavioral atypicality, anxiety and depression in children with chromosome 22q11.2 deletion syndrome

Abstract: Chromosome 22q11.2 deletion syndrome (22q11.2DS) is a complex developmental disorder with serious medical, cognitive and emotional symptoms across the lifespan. This genetic deletion also imparts a lifetime risk for developing schizophrenia that is 25–30 times that of the general population. The origin of this risk is multifactorial and may include dysregulation of the stress response and immunological systems in relation to brain development. Vitamin D is involved in brain development and neuroprotection, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 101 publications
(163 reference statements)
0
12
0
Order By: Relevance
“…27 Recently, it has been reported that low vitamin D levels are associated with schizophrenia, depression, and anxiety in the general population. 28 In a cohort study conducted between 2015 and 2017, Fond et al 29 reported hypovitaminosis D in 21.4% of the subjects with no vitamin D supplementation during the previous 12 months. Additionally, this hypovitaminosis D was severely associated with depressive and anxiety symptoms; however, vitamin D supplementation significantly improved these symptoms.…”
Section: Correlations Between the 25(oh)d And Tsh Levels And The Bdi-mentioning
confidence: 99%
“…27 Recently, it has been reported that low vitamin D levels are associated with schizophrenia, depression, and anxiety in the general population. 28 In a cohort study conducted between 2015 and 2017, Fond et al 29 reported hypovitaminosis D in 21.4% of the subjects with no vitamin D supplementation during the previous 12 months. Additionally, this hypovitaminosis D was severely associated with depressive and anxiety symptoms; however, vitamin D supplementation significantly improved these symptoms.…”
Section: Correlations Between the 25(oh)d And Tsh Levels And The Bdi-mentioning
confidence: 99%
“…Kelly L conducted a study which demonstrated that vitamin D insufficiency might relate to higher levels of anxiety and depression, in turn contributing to the elevated risk of psychosis in children with chromosome 22q11.2 deletion syndrome (22q11.2DS). This syndrome is a complex developmental disorder with serious medical, cognitive and emotional symptoms in their lifespan [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…Among the different mechanisms by which hypoparathyroidism contributes to hypocalcemia, there is inadequate renal conversion of 25‐hydroxyvitamin D to 1,25‐dihydroxyvitamin D (calcitriol), the active metabolite of vitamin D, which is necessary for intestinal absorption of calcium [21]. Therefore, these patients require treatment with calcium carbonate and calcitriol to correct hypocalcemia [20,22,23].…”
Section: Introductionmentioning
confidence: 99%